PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR MATEMATIKA KELAS VIII DI SEKOLAH SMP SWASTA PGRI 19 LOHSARI BARAT: PENGARUH MODEL PROBLEM-BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR MATEMATIKA DI SMPS PGRI 19 LOHSARI BARAT - Adella, Priti; Hasibuan, Lily Rohanita; Eva Julyanti (Department of Mathematics Education Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2024)
The background to this research is the low level of mathematics learning outcomes and critical thinking abilities. The need for influential learning to support critical thinking skills and student learning outcomes through the problem-based learning model. This research aims to determine the effect of the problem-based learning model on students' critical thinking abilities and mathematics learning outcomes. The research was carried out at PGRI 19 West Lohsari Private Junior High School. This research is a quasi-experimental type with a Non-Equivalent Control Group Pretest-Posttest Design. The subjects in this research consisted of two classes, namely class VIII-1 with a total of 26 students as an experimental class treated using a problem-based learning model and class VIII-2 with a total of 26 students as a control class using a conventional learning model. The data analysis technique used is the t-test or paired sample t-test. The instrument used is a test in the form of an essay to measure critical thinking abilities and mathematics learning outcomes. The results of hypothesis testing using the t-test obtained a value of t-count 8.33431 > t-table = 0.388, which means that there is a significant influence of the application of the problem-based learning model on critical thinking skills and mathematics learning outcomes for class VIII at PGRI 19 West Lohsari Private Junior High School. The Problem-Based Learning model has been associated with several advantages, such as improving critical thinking skills, improving problem-solving abilities, and improving mathematics learning outcomes. Thus, the problem-based learning model can be effective in improving students' critical thinking skills and mathematics learning outcomes.